2013
DOI: 10.1016/j.bpj.2013.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitivity by Molecular Titration in Spatially Propagating Enzymatic Reactions

Abstract: Delineating design principles of biological systems by reconstitution of purified components offers a platform to gauge the influence of critical physicochemical parameters on minimal biological systems of reduced complexity. Here we unravel the effect of strong reversible inhibitors on the spatiotemporal propagation of enzymatic reactions in a confined environment in vitro. We use micropatterned, enzyme-laden agarose gels which are stamped on polyacrylamide films containing immobilized substrates and reversib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 67 publications
0
25
0
Order By: Relevance
“…Synthetic reaction-diffusion systems can also produce spatiotemporal chemical patterns from the bottom up, using inorganic systems such as the Belousov-Zhabotinsky reaction, 22,23 or enzymatic networks [24][25][26][27][28][29] both with transcriptional circuits 30 and with the Polymerase, Exonuclease, Nickase (PEN) toolbox, 31,32 including gradients, traveling waves and spatial patterns of spots or stripes. 33,34 However, the kinetics of many enzyme-based RD systems are sensitive to temperature variations of a few C and to buffer conditions, limiting when they can be applied.…”
Section: -14mentioning
confidence: 99%
“…Synthetic reaction-diffusion systems can also produce spatiotemporal chemical patterns from the bottom up, using inorganic systems such as the Belousov-Zhabotinsky reaction, 22,23 or enzymatic networks [24][25][26][27][28][29] both with transcriptional circuits 30 and with the Polymerase, Exonuclease, Nickase (PEN) toolbox, 31,32 including gradients, traveling waves and spatial patterns of spots or stripes. 33,34 However, the kinetics of many enzyme-based RD systems are sensitive to temperature variations of a few C and to buffer conditions, limiting when they can be applied.…”
Section: -14mentioning
confidence: 99%
“…Cr does not cleave C 1 (Figure S21 of the SI), but rapidly cleaves thioester 3 , activating the formation of C 2 . Finally, the enzymatic network is deactivated by the presence of soybean trypsin inhibitor (STI) protein, a strong, reversible inhibitor of Tr ( K D 1 n m ) that sets a threshold for the Tr input that will activate the network. We found that STI also reversibly inhibits Cr ( K D =634 n m , Figure S14), but with a dissociation constant at least two orders of magnitude larger than for Tr.…”
Section: Figurementioning
confidence: 99%
“…Extending the work by de Greef & Huck et al (vide supra), 40 positive feedback was added to the trypsin-inhibitor system by employing trypsinogen, a zymogen that is autocatalytically cleaved into trypsin. Similarly, Huck and colleagues 42 combined enzymatic autocatalysis and molecular titration to develop a system which is able to sense the spatial distribution of enzymes.…”
Section: View Article Onlinementioning
confidence: 99%